Propelling Sales in Adverse Condition in a Distribution Company: A Literature Review (Global Journal of Management and Business Research, 2021)
With the growing and numerous distributors that compete in the market, the distribution company is measured on how it can propel sales in a regular or adverse condition. The salespersons and other related personnel of the company are accountable for delivering the sales to customers. The goal of this review is to evaluate issues encountered when propelling sales in the adverse conditions in a distribution company as it examined articles posted in on-line international journals from 2013 to 2020. It focuses on the findings of some articles when propelling sales in adverse conditions, particularly the accountability of the personnel in the Sales organization.
Keywords: adverse condition; distribution company; propelling sales; sales